Performance of RHA Cement Concrete under Marine Environment via Wetting and Drying Cyclic by Rapid Migration Test - Putra Jaya, Ramadhansyah; Wan Ibrahim, Mohd Haziman; S. J, Dewi; B. H, Abu Bakar; M. Z. M, Salwa (International Journal of Integrated Engineering, 2013)
In this research, the performance of concrete containing rice husk ash (RHA) under marine environment through wetting and drying cycles was investigated. Five levels of cement replacement (0%, 10%, 20%, 30% and 40% by weight) were used. The total cementitious content used was 420 kg/m3. A water/binder ratio of 0.49 was used to produce concrete having a target compressive strength of 40MPa at the age of 28 days. The performance of blended cement concrete under marine environment was evaluated using rapid migration test (RMT).  The results clearly showed that RHA can be satisfactorily used as a cement replacement material in order to reduce the chloride penetration depth and hence increases the durability of concrete. Generally, the chloride penetration depth of concrete containing higher RHA replacement is decreased as the RHA replacement increases, resulting in concrete with higher resistance to seawater attack.